Activation barriers and rate constants for hydration of platinum and palladium square-planar complexes: an ab initio study - Burda, Jaroslav V; Zeizinger, Michal; Leszczynski, Jerzy (The Journal of chemical physics, 2004)
In the present work, an ab initio study on hydration (a metal-ligand replacement by water molecule or OH- group) of cis- and transplatin and their palladium analogs was performed within a neutral pseudomolecule approach (e.g., metal-complex+water as reactant complex). Subsequent replacement of the second ligand was considered. Optimizations were performed at the MP2/6-31+G(d) level with single-point energy evaluation using the CCSD(T)/6-31++G(d,p) approach. For the obtained structures of reactants, transition states (TS's), and products, both thermodynamic (reaction energies and Gibbs energies) and kinetic (rate constants) characteristics were estimated. It was found that all the hydration processes are mildly endothermic reactions-in the first step they require 8.7 and 10.2 kcal/mol for ammonium and chloride replacement in cisplatin and 13.8 and 17.8 kcal/mol in the transplatin case, respectively. Corresponding energies for cispalladium amount to 5.2 and 9.8 kcal/mol, and 11.0 and 17.7 kcal/mol for transpalladium. Based on vibrational analyses at MP2/6-31+G(d) level, transition state theory rate constants were computed for all the hydration reactions. A qualitative agreement between the predicted and known experimental data was achieved. It was also found that the close similarities in reaction thermodynamics of both Pd(II) and Pt(II) complexes (average difference for all the hydration reactions are approximately 1.8 kcal/mol) do not correspond to the TS characteristics. The TS energies for examined Pd(II) complexes are about 9.7 kcal/mol lower in comparison with the Pt analogs. This leads to 10(6) times faster reaction course in the Pd cases. This is by 1 or 2 orders of magnitude more than the results based on experimental measurements.
Keywords: Models, Molecular; teplota; chloridy; Quaternary Ammonium Compounds; Water; cisplatina; Cisplatin; Molecular Structure; voda; termodynamika; molekulární konformace; chemické modely; Platinum; Ligands; molekulární modely; kvartérní amoniové sloučeniny; platina; ligandy; Kinetics; Molecular Conformation; palladium; Chlorides; kinetika; Palladium; Thermodynamics; fyzikální chemie; Chemistry, Physical; molekulární struktura; Temperature; Models, Chemical